Results of the project FLAVIA in the action plan for terminal development - Bulíček, Josef; Nachtigall, Petr; Široký, Jaromír; Cempírek, Václav (Univerzita Pardubice, 2013)
During the project FLAVIA was found that support of logistics and intermodal transport in the direction Germany - Black Sea has to be done not only by multimillion-dollar investments, but there might be done a number of sub-measures, which will have the synergic effect and support logistics. In support of this decision has been compiled this report. University of Pardubice was responsible for that report. There are described various shortcomings in the development of combined transport terminals. This article is summarizing conclusions of this report.
Výsledky projektu FLAVIA - akční plán pro rozvoj logistických terminálů
Die ergebnisse von dem projekt FLAVIA – ein aktionsplan für die terminalentwicklung